Synergistic effects of dimethyl sulfoxide-treatment and aramid nanofiber addition on performance enhancement of the PEDOT: PSS-based supercapacitor - Xuening Jiang; Yuxin Sun; Yige He; Xueping Zhao; Xinyu Zhu; Lei Jiang (Journal of Science: Advanced Materials and Devices, 2024)
Charge storage performance of the poly (3,4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT: PSS, PH1000)-based supercapacitor is greatly enhanced by dimethyl sulfoxide (DMSO)-treatment and addition of aramid nanofibers (ANFs), but the underlying mechanism is unclear. To reveal it, we synthesized the films of PH1000, DMSO-treated PH1000 (D-P) and DMSO-treated PH1000-20 wt%ANF (D-PA) to construct the in-plane supercapacitors. A comparative study of electrochemical performance was firstly conducted to identify the specific contribution of DMSO-treatment and ANF components. Electrochemical impedance spectroscopy (EIS) was then analyzed, and the results demonstrated that the reduction of the ohmic resistance of the device was mainly attributed to the DMSO-treatment, while the addition of ANFs was found to contribute more to the decrease of Warburg resistance. The effects of DMSO-treatment and ANF components on the electrical propertíe and microstructure of PH1000 film were analyzed based on the square resistance results and AFM/SEM images, respectively. Dynamic permeation processes of the hydrogel electrolyte on the films were further recorded, vividly showing that the electrolyte permeability is highly dependent on the microstructure of the film. Through these analyses, a deep insight into the synergistic effects of DMSO-treatment and ANF addition on the electrochemical performance of the PH1000-based supercapacitor has been reached.